پاكستان مىں جاگىر دارانہ نظام كا شرعى وتارىخى تناظر مىں تحقىقى وتجزىاتى جائزہ - Rizwan Ullah; Dost Muhammad Khan (Pakistan Journal of Islamic Research)
Pakistan is suffering by the weak land reforms from its birth till now and there is a serious issue regarding the rules and regulations for land distribution among the citizens, as most of the land of this region was distributed with a political distort by the British men. The society has been driven by the combination of legal and military customs indirectly, which upshots in feudal oriented society where a few people became the possessors and masters of the whole society. With the passage of time these people gains much more power and they play a key role in land occupation which results in the exploitation of public interest. This special class of the society even plays a persuasive and pivotal role in addressing and designing the political, economic, social, cultural, and moral values merely for themselves only. The reflection and repercussions of such like feudalism are the root cause of the asymmetry in Pakistani society. This paper will elaborate the historical and current aspects of feudal system in the result of land distribution by the British government and illustrate it with the Islamic laws to critically analyze upon the present situation of Pakistan.